Innovative Assessment Based on Augmented Reality (AR) in Early Childhood Education: Development of A Holistic Assessment Model for Young Children - Aminulloh Aminulloh; Marwah Marwah; Mimi Hilmiah; Rahmat Rahmat; Zuhriyah Zuhriyah; Abdul Hamid (Pelopor Publikasi Akademika, 2026)
Digital transformation in early childhood education requires innovative assessment practices that emphasize not only learning outcomes but also learning processes and holistic child development. This research aims to develop and analyze an innovative assessment model based on Augmented Reality (AR) and digital interaction in Islamic kindergarten (Raudhatul Athfal). The study employed a Research and Development (R&D) method using the ADDIE model. The participants included 20 children aged 5–6 years and two Raudhatul Athfal teachers at Al-Mansyuriah Bekasi. Data were collected through interactive observation, digital portfolios, and teacher questionnaires and analyzed using descriptive statistics and thematic analysis. The findings indicate that AR-based assessment enhances children's learning engagement, improves teachers' assessment efficiency, and produces more objective and well-documented assessment data. This model is relevant for supporting authentic assessment and strengthening Islamic values in early childhood education. In conclusion, the AR-based holistic assessment model is effective in capturing children's cognitive, social-emotional, linguistic, and moral development comprehensively, while also addressing the limitations of conventional manual assessments by providing a more interactive, systematic, and documentation-friendly approach that aligns with both digital era needs and Islamic educational values.